Role Of Health Education Through Media in Prevention Of Covid-19 Pandemic (Saida And Tyr Provinces) - El Haj Mousa, Alaa; Awwad, Khodor (International Journal of Scientific Research and Management (IJSRM), 2023)
The main objective of this study is to examine the role of health education through the media prevention of (COVID-19) in the two designated cities (Saida and Tyr). The study's foundational data comes from a survey administered to residents of Saida and Tyr and was gathered using a quantitative methodology that combines cross-sectional and descriptive designs. 460 online surveys were submitted by residents of the two cities. The study hypotheses were further examined with the use of an Anova Test, an Independent T-test, and a Pearson correlation analysis. The results demonstrated a beneficial association between health education via the media and the avoidance of (COVID-19). The study reached also a set of conclusions, among which are: It is found out that the majority of the sample individuals prefer to use social media as main source of for prevention of COVID-19. It appears too that the majority of the sample individuals spend more than 2 hours in using media channels for to follow health information’s and health programs.  The respondents have also an agreement with most of the information required about their behavioral skills during the pandemic, and have an agreement with most of the information required about the trust of information’s provided by media channels that help them to change the behavioral and cognitive prevention. This is the first study that examines the role of health education through media in prevention during COVID-19 pandemic across the two selected cities (saida and Tyr).